2010
DOI: 10.1038/jcbfm.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

Wide Genetic Variation in the Native Pial Collateral Circulation is a Major Determinant of Variation in Severity of Stroke

Abstract: Severity of stroke varies widely among individuals. Whether differences in the extent of the native (preexisting) pial collateral circulation exist and contribute to this variability is unknown. We addressed these questions and probed for potential genetic contributions using morphometric analysis of the collateral circulation in 15 inbred mouse strains recently shown to exhibit wide differences in infarct volume. Morphometrics were determined in the unligated left hemisphere (for native collaterals) and ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
383
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(434 citation statements)
references
References 38 publications
43
383
1
2
Order By: Relevance
“…Overall, 37.6% had good (17)(18)(19)(20), 40.5% had medium (11)(12)(13)(14)(15)(16), and 21.7% had poor (0 -10) rLMC scores. Median stroke onset to CTA time was 164 minutes; most patients (75%) were scanned at 361 or fewer minutes after stroke onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 37.6% had good (17)(18)(19)(20), 40.5% had medium (11)(12)(13)(14)(15)(16), and 21.7% had poor (0 -10) rLMC scores. Median stroke onset to CTA time was 164 minutes; most patients (75%) were scanned at 361 or fewer minutes after stroke onset.…”
Section: Resultsmentioning
confidence: 99%
“…Higher rLMC score was significantly correlated with lower baseline NIHSS (Spearman r ϭ Ϫ0.36; 95% CI, Ϫ0.50% to Ϫ0.21%; P Ͻ .001) and with lower mRS at 3 months (Spearman r ϭ Ϫ0.47; 95% CI, Ϫ0.59% to Ϫ0.33%; P Ͻ .001). Good clinical outcome was seen in 52% of patients with good rLMC score (17)(18)(19)(20), 34% with medium rLMC score (11)(12)(13)(14)(15)(16), and 7% with poor rLMC score (0 -10) (P Ͻ .001). In univariate analysis, higher rLMC score, lower age, lower baseline NIHSS, higher baseline ASPECTS and CTAsi ASPECTS, higher clot burden score, and any endovascular therapy (IA alone or IV ϩ IA tPA or mechanical) were associated with good clinical outcome (On-line Table 1).…”
Section: Variables Associated With Good Clinical Outcome Mrs <2mentioning
confidence: 90%
“…5C). Long-term changes in the vasculature could compensate for this hypoperfusion and ameliorate potential damage at threshold levels of flow (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results of this group have to be compared with the other groups with care. It has been shown that infarct volumes and cerebrovascular anatomy vary with genetic background 11,12 and larger infarcts have been observed in the C57Bl/6 compared with the SV129 strain. 41 However, a study by Pham et al found no differences of infarct sizes, ADC, or CBF at any time point between SV129 and C57Bl/6 mice after transient MCAO.…”
Section: Weaknesses Of Our Studymentioning
confidence: 99%
“…Despite these advantages, variability of infarct sizes is substantial, owing to the variability of the surgical procedure 8,9 and interanimal variability of brain blood vessel anatomy [10][11][12] among other factors. Because of the substantial infarct size variability (SDs usually ≈30% of the mean) and small group sizes (between 4 and 10) in experimental stroke research, it is likely that false-positive results and an overestimation of effect sizes abound in publications.…”
Section: Strokementioning
confidence: 99%